Spatiotemporal dynamics of dengue hotspots in an urbanizing landscape: a five-year analysis in Selangor, Malaysia - Mohd Hardy Abdullah, Nur Athen; Che Dom, Nazri; Salleh, Siti Aekbal; Salim, Hasber; Precha, Nopadol; Dapari, Rahmat (Elsevier B.V., 2025)
Introduction: Spatial analysis plays a crucial role in vector control by assessing disease dynamics and identifying risk areas. While numerous studies have examined dengue incidence in Malaysia, few have specifically investigated prolonged localized dengue epidemics lasting more than 30 days. This study aims to analyze the distribution and patterns of dengue hotspots in Selangor from 2017 to 2021. Methods: Dengue hotspot coordinates were obtained from Google Maps and mapped using ArcGIS. Heat maps were generated to visualize temporal and spatial hotspot patterns across epidemiological weeks and districts. Hotspot analysis was conducted to identify areas with a high frequency of dengue cases. Results: Over 400 dengue hotspots were identified, primarily concentrated in Gombak, Hulu Langat, Klang, and Petaling districts characterized by high population densities exceeding 1000 individuals per km2. Peak dengue hotspot occurrences (≥70 per week) were observed during three seasonal periods: January–March, June–September, and October–December. Conclusion: This study provides new insights into the spatial-temporal distribution of prolonged dengue outbreaks in Selangor. The findings can inform targeted vector control strategies and policy interventions in high-risk areas.